Urgensi Perjanjian Perkawin dalam Upaya Suami atau Istri Tidak Terpenuhinya Kewajiban Atas Harta Bersama - Nabila Eka Pratama Putri Nurhidayat; Indratirini Indratirini (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The legal consequence of a marriage is that the wife's property becomes the husband's property, and vice versa, this is the beginning of what is called joint property. However, there are efforts to separate inherited assets between the husband's assets and the wife's assets. The Marriage Agreement between Mr. PAT and Mrs. P is about the husband's obligations and the wife's rights, such as when the marriage takes place, objects that are not in the husband's name become the property of the wife. The formulation of the problem that arises is whether the legal recourse if joint property objects which cannot be proven to be owned in the husband's name will become the property of the wife and what legal remedies can be taken if one party does not carry out its obligations in accordance with the contents of the agreement. The research method used is normative law by examining statutory regulations and the articles in the marriage agreement between Mr. PAT and Mrs. P which contain legal issues regarding joint property. The results of the research show that there are no regulations which stipulate that joint objects which cannot be proven to be in the name of the husband may not belong to the wife or his heirs, the Marriage Agreement is a halal cause and does not conflict with anything. The legal remedy if there is a violation of the marriage agreement is a lawsuit for breach of contract or you can file a lawsuit for divorce/talak in the District Court according to the contents of the marriage agreement.